Effects of Dental Implants and Nutrition on Elderly Edentulous Subjects: Protocol for a Factorial Randomized Clinical Trial - Qian, Shu-Jiao; Liu, Beilei; Shi, Junyu; Zhang, Xiao; Deng, Ke; Shen, Jie; Tao, Yang; Qiao, Shichong; Lai, Hong-Chang; Yuan, Changzheng; Tonetti, Maurizio S. (Frontiers in Nutrition, 2022)
Background: Loss of masticatory function consequent to tooth loss has been associated with changes in food choices and insufficient nutritional intake. To date, interventions based on dental prostheses alone did not significantly improve nutrient intake. Pilot studies have shown positive impacts of interventions combining implant-supported fixed dental prosthesis with brief dietary advice. The relative contribution and the potential synergy of the components of such interventions need to be determined as it has major public health implications for the community-dwelling ageing population that continues to disproportionately suffer from tooth loss and its consequences. Objective：To assess the effect of rehabilitation of masticatory function with fixed implant supported dentures and nutrition education in older subjects with terminal dentition (stage IV periodontitis) or full edentulism. Methods: A 2 × 2 factorial randomized controlled trial of eligible adults (≥60 years) with loss of masticatory function consequent to full arch edentulism or terminal dentition (n = 120) will be conducted to test whether the rehabilitation of masticatory function with fixed implant supported dentures, nutrition education and/or their combination improves intake of fresh fruits and vegetables for ageing subjects. The study has been designed to detect changes in fresh fruits and fresh vegetables intake at 4 months using the 24-hour dietary recall method. Changes in protein as percentage of total energy, nutritional biomarkers, plasma metabolomics, oral and gut microbiome, quality of life and masticatory function will also be assessed. Discussion: We hypothesize that receiving rehabilitation of masticatory function with fixed implant dentures together with nutrition education is the most effective intervention for improving nutrient intake in ageing community-dwelling subjects with extensive tooth loss. Clinical Trials Registration：NCT05334407